MENGGALI NILAI-NILAI HAKIKI DALAM PENDIDIKAN ISLAM - Noviani, Dwi; Destyaningsi, Rosalina; Yunika, Dhea; Rosalia, Meta (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Islamic education plays a fundamental role in shaping individuals who are not only intellectually superior but also spiritually and morally strong. This study begins with the importance of rediscovering the essential values within the Islamic education system, whose meaning is often diminished. The primary focus of this research is to investigate essential values such as the nature of life as worship, the goal of education to achieve happiness in this world and the hereafter, and self-purification (tazkiyah) and the attainment of perfection (ihsan). Using library research methods, this study collected and analyzed data from various scientific journals to explore these key concepts. Key findings indicate that core values such as faith, piety, noble character, and humanity are integral foundations of the Islamic education process. Furthermore, this study found that the Quran, Hadith, and scholarly traditions such as madrasas and Islamic boarding schools (pesantren) are the primary foundations for shaping character and morals. In conclusion, the holistic integration of these essential values is key to improving the quality of Islamic education and producing a generation of noble character capable of fulfilling their role as caliphs on earth. ABSTRAKPendidikan Islam memegang peranan fundamental dalam membentuk individu yang tidak hanya unggul secara intelektual tetapi juga kokoh secara spiritual dan moral. Studi ini berangkat dari latar belakang pentingnya penggalian kembali nilai-nilai hakiki dalam sistem pendidikan Islam yang seringkali tereduksi maknanya. Fokus utama penelitian ini adalah untuk menginvestigasi nilai-nilai esensial seperti hakikat kehidupan sebagai ibadah, tujuan pendidikan untuk mencapai kebahagiaan dunia dan akhirat, serta penyucian diri (tazkiyah) dan pencapaian kesempurnaan (ihsan). Menggunakan metode penelitian pustaka, studi ini mengumpulkan dan menganalisis data dari berbagai jurnal ilmiah untuk mendalami konsep-konsep kunci tersebut. Temuan utama menunjukkan bahwa nilai-nilai inti seperti keimanan, ketakwaan, akhlak mulia, dan kemanusiaan adalah fondasi yang tidak terpisahkan dari proses pendidikan Islam. Lebih lanjut, penelitian ini menemukan bahwa Al-Qur'an, Hadis, serta tradisi keilmuan seperti madrasah dan pesantren merupakan dasar utama yang membentuk karakter dan moral. Kesimpulannya, pengintegrasian nilai-nilai hakiki ini secara holistik merupakan kunci untuk meningkatkan mutu pendidikan Islam dan mencetak generasi berakhlak mulia yang mampu menjalankan perannya sebagai khalifah di bumi.